Radioiodine (131i) Therapy for Thyrotoxicosis Patients and their Outcome: Experience at Center for Nuclear Medicine & Ultrasound, Barisal - Biswas, Shankar Kumar; Jahan, Nafisa; Rahman, KBM Abdur (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Radioiodine therapy appears to be an effective means in controlling thyrotoxicosis and it acts either by destroying functioning thyroid cells or by inhibiting their ability to replicate. The variable radiosensitivity of the gland means that the choice of dose is empirical. Unfortunately all attempts at dosimetry have thus far failed to reliably deliver a dose that avoids recurrence and does not ultimately lead to hypothyroidism. Ninety five patients (female 66 and male 29) with thyrotoxicosis treated with radioiodine at the Center for Nuclear Medicine & Ultrasound, Barisal and their outcome were analyzed from January 2000 to December 2004. Before radioiodine administration clinical features of the patients, palpation of the thyroid gland and ultrasonogram were performed. 131I was given as fixed dose method and the dose ranged from 8-12 mCi. Higher doses were administered for larger goiter, multinodular goiter and in relapse cases. Hyperthyroid state was controlled in 85 (89%) patients after receiving single dose of radioiodine and 13 (13.6%) patients developed hypothyroidism within 3 months of therapy. Radioiodine therapy has proved to be cheap and effective method of treatment for thyrotoxicosis. Key words: Thyrotoxicosis, Radioiodine therapy, Hypothyroidism. DOI: 10.3329/jbcps.v26i2.4184 J Bangladesh Coll Phys Surg 2008; 26: 73-78